The Effect of Inlet Notch Variations in Pico-hydro Power Plants with Experimental Methods to Obtain Optimal Turbine Speed - Naufal Praska Zakariz; Anggara Trisna Nugraha; Khongdet Phasinam (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2022)
ABSTRACT Energy is an important element in the continuity of human activities. Indonesia has the potential to produce 94.5 GW of electricity in the hydropower sector, but only a few can be utilized, which is only 11%. This study aims to utilize renewable energy that has not been utilized optimally, especially in Indonesia. This study exploits the potential of water flow from the Coban Wonoasri River, Bangun Village, Munjungan District, Trenggalek Regency which has a low head but has a fairly heavy discharge. The basin cone for making vortex flow has a canal length of 1450 mm, a canal width of 231.5 mm, and a canal height of 500 mm with a basin cone diameter of 560 mm, a basin cone height of 700 mm, and a water outlet diameter of 90 mm. A vortex turbine with a diameter of 270 mm and a height of 210 mm with a total of 8 blades, a blade curvature of 30°, and a blade tilt of 22.5° was used for research on this low head river. The inlet notch variations that will be used are angles of 0°, 17.82°, 19.30°, and 19.98°. The method used in this study is the experimental method, where the best results are obtained from the results of tests carried out on variations in the inlet notch. The inlet notch with a width of 0° and a discharge of 8.81 l/s cannot produce turbine rotation because the vortex flow is not formed properly. Inlet notch with a width of 17.82° and 19.30° produces an average turbine speed of 157.2 rpm and 159.2 rpm. The variation of the inlet notch with a width of 19.98° produces the best turbine speed of 162.7 rpm with a flow rate of 7.72 l/s.